Cardiac birth defects induced by maternal medications - Koren, Gideon (Prenatal Cardiology, 2020)
Cardiovascular malformations form the largest group of congenital anomalies, typically quoted at 0.8% of all live births. Several medicinal drugs have been proven to cause cardiovascular malformations. We discuss here the risks of the major known medications, including lithium, valproic acid, ondansetron, methylphenidate, topiramate, and the newly recognised dydrogesterone. In contrast, we discuss the controversial and debated effects of selective serotonin reuptake inhibitors (SSR) and selective serotonin norepinephrine reuptake inhibitors (SNRI). Subsequently we describe the principles of counselling pregnant women and those planning pregnancy, who are exposed to these drugs.